THE CONCEPT OF HUMAN NATURE AND ITS CHALLENGES IN DEVELOPING INDIVIDUAL POTENTIAL IN THE DIGITAL ERA: KONSEP HAKIKAT MANUSIA DAN TANTANGANNYA DALAM PENGEMBANGAN POTENSI INDIVIDU DI ERA DIGITAL - Shaza Fajhira; Dyah Kumalasari (SOSIOEDUKASI, 2025)
This study aims to examine the fundamental nature of human beings, the role of environment and education in developing individual potential, and its implications for societal development. Using a literature review method, this research analyzes various sources from philosophical, scientific, social, and cultural perspectives. The findings indicate that humans, as rational, social, and ethical beings, possess unique potentials that can be nurtured through education, a supportive environment, and moral and spiritual values. Education serves as a key instrument in shaping character, fostering moral intelligence, and preparing individuals to face global dynamics. In the digital era, challenges and opportunities emerge alongside rapid technological advancement and social change. Therefore, a holistic approach is required—one that fosters synergy among education, social environment, and human-centered public policies. A deeper understanding of human nature can help build a more just, inclusive, and sustainable society. The study recommends strengthening character education, reinforcing social and cultural values, adapting to technological change, and promoting policies focused on human well-being.